Pengaruh Penerapan Program Kuis dalam Pembelajaran Bahasa Arab Terhadap Hasil Belajar Siswa MTs Tarakan - Mustamin Mustamin; Muhammad Anhar; Radika Maharani (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The background of this research is the low learning outcomes of online students in the seventh grade Arabic subject at Madrasah Tsanawiyah Negeri Tarakan. One of the learning media that can improve online learning outcomes is the android quizziz learning media. The goal to be achieved is to determine the effect of the quizziz android game application in learning Arabic on learning outcomes for class VII MTs Negeri Tarakan students. This study uses a quantitative research approach and the type of research used is a quasi-experimental design with a nonequivalent control group design. The research sample used was class VII C as the experimental class and class VII D as the control class. Research data obtained from the results of pretest and posttest with multiple choice questions to measure student learning outcomes. Analysis of research data using T-test with the formula Independence Sample T-Test. The results showed that there was a significant influence on the use of quizziz android application media on learning outcomes for seventh grade students at MTs Negeri Tarakan. This is in accordance with the results of hypothesis testing, the significance value (Sig.2-tailed) is 0.018 <0.05, thus Ha is declared accepted and Ho is declared rejected. Thus, it can be concluded that there is an influence of the quizziz android application learning media on the learning outcomes of class VII students at MTs Negeri Tarakan.